Max phase based saturable absorber for mode-locked erbium-doped fiber laser - Jafri, A. A. A. (Elsevier Ltd., 2020)
We presented an ultrashort pulse generation in an erbium-doped fiber laser cavity using MAX-PVA as a mode-locker. A thin film of SA was prepared by mixing PVA with Ti3AlC2 as a saturable absorber inside the laser cavity. The optical nonlinearity was also demonstrated, revealing a saturable absorption of 2%, a non-saturable absorption of 58.2%, and a saturation intensity of 1.63 MW/cm2. The excellencies of MAX-PVA was proven as it initiates ultrafast laser with a duration of 3.68 ps corresponds to a repetition rate of 1.887 MHz. The ease of preparation, together with its superior optical, physical, thermal, and mechanical properties, makes it a favorable SA for pulse generation in an all-fiberized laser cavity.